An Effective Attendance Monitoring System with Fraud Prevention Technique for Educational Institutions - Qaiduzzaman, Khandker M; Shahjahan, Mohammad; Sobhan, Sadman; Arman, Md. Shohel; Taj Noor, Manan Binth; Rahman, Mostafijur (International Journal of Engineering and Technology, 2018)
In this article, an Attendance Monitoring System (AMS) is proposed for educational institutions. The novel aspect of this work is to integrate a password-protected attendance counting module with the system. The module can effectively limit the fraudulent activities in attendance monitoring process. Besides that, some constraints are proposed to increase the security of the AMS. Based on the constraints a new system is designed to maintain the attendance data and the user information. The aim of this research is to design an effective AMS using the Radio Frequency Identification (RFID) technology to prevent fraudulence. Besides, the attention is given to the usability and the efficiency of the system. For this purpose, a usability testing named System Usability Scale (SUS) is used after implementing the system in the real world. The usability test result shows that the proposed system has an average SUS score of 71.92 out of 100. The score indicates that the proposed system has the adjective rating, â€œgoodâ€ (range 71.4 â€“ 85.5). A performance testing is conducted by calculating the average response time for the system. The response time is collected by varying the number of RFID tags and the lengths of the serial cable. The average response time of the proposed system is found 1.11 second which is better than the traditional paper-based system.
Keywords: Attendance monitoring; fraud prevention; RFID; radio frequency identification; student attendance